Strategi Guru PAI dalam Mengatasi Kesulitan Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam - Afreza Lailatun Nazalah; Aufia Aisa; Dian Kusuma Wardani (ANWARUL, 2026)
Although learning difficulties in Islamic education have been widely examined, studies that specifically discuss teachers’ strategies in overcoming learning difficulties in the Islamic Cultural History (SKI) subject at the MTs level remain limited. This study aims to describe the forms of students’ learning difficulties, the obstacles faced by teachers, and the strategies implemented by teachers in overcoming learning difficulties in the SKI subject. This study used a qualitative approach with a descriptive design, involving one SKI teacher and three Grade VII students at MTs Darul Ulum Kepuhdoko Jombang as informants selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that students experienced difficulties in understanding the chronological sequence of historical events, memorizing the names of figures and years, low reading interest, and lack of concentration during learning. The obstacles faced by the teacher included limited learning media, heterogeneous student abilities, and inadequate learning time. The strategies implemented by the teacher included group discussions, individual and group presentations, repeated practice or drills, motivational approaches, and the use of simple media such as timelines and written summaries. These strategies helped reduce some of students’ learning difficulties, although innovation in learning methods and media is still needed. The conclusion of this study emphasizes the importance of teachers’ strategic creativity in improving the effectiveness of SKI learning. The implications of this study provide theoretical contributions to the development of the literature on Islamic Religious Education learning strategies and practical guidance for teachers and educational institutions in developing more interactive and contextual SKI learning.